2016
DOI: 10.1371/journal.pone.0164302
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and Zinc Status in Chronic Myofascial Pain: Serum and Erythrocyte Concentrations and Food Intake

Abstract: IntroductionNutritional disorders have been reported to be important causal factors that can intensify or cause a painful response in individuals with chronic musculoskeletal pain.AimTo assess the habitual intake of and the serum and erythrocyte levels of selenium and zinc in patients with chronic myofascial pain.Materials and MethodsA case-control study of 31 patients with chronic myofascial pain (group I) and 31 subjects without pain (group II). Dietary record in five days for assessing food intake were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…In humans, an inadequate intake of both Zn and Se and their low intracellular stores are correlated with pain in patients with chronic myofascial pain ( 220 ) .…”
Section: Resultsmentioning
confidence: 99%
“…In humans, an inadequate intake of both Zn and Se and their low intracellular stores are correlated with pain in patients with chronic myofascial pain ( 220 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Barros-Neto et al . [ 160 ] investigated the relationship between chronic musculoskeletal pain and malnutrition and reported that myofascial pain is associated with changes in intracellular zinc and selenium stores caused by inadequate food intake.…”
Section: Selenium and Painmentioning
confidence: 99%
“…Moreover, serum magnesium and zinc levels are also associated with clinical parameters in FM, indicating their potential role in the pathogenesis of the disease. [9][10][11][12] Zinc is an essential element required for various systems to function properly. It naturally exists in some foods and is also available as a dietary supplement.…”
Section: Introductionmentioning
confidence: 99%